Evolutionary Adaptations of Parasitic Flatworms to Different Oxygen Tensions - José de Jesús Martínez-González; Alberto Guevara-Flores; Irene Patricia del Arenal Mena (MDPI AG, 2022)
During the evolution of the Earth, the increase in the atmospheric concentration of oxygen gave rise to the development of organisms with aerobic metabolism, which utilized this molecule as the ultimate electron acceptor, whereas other organisms maintained an anaerobic metabolism. Platyhelminthes exhibit both aerobic and anaerobic metabolism depending on the availability of oxygen in their environment and/or due to differential oxygen tensions during certain stages of their life cycle. As these organisms do not have a circulatory system, gas exchange occurs by the passive diffusion through their body wall. Consequently, the flatworms developed several adaptations related to the oxygen gradient that is established between the aerobic tegument and the cellular parenchyma that is mostly anaerobic. Because of the aerobic metabolism, hydrogen peroxide (H2O2) is produced in abundance. Catalase usually scavenges H2O2 in mammals; however, this enzyme is absent in parasitic platyhelminths. Thus, the architecture of the antioxidant systems is different, depending primarily on the superoxide dismutase, glutathione peroxidase, and peroxiredoxin enzymes represented mainly in the tegument. Here, we discuss the adaptations that parasitic flatworms have developed to be able to transit from the different metabolic conditions to those they are exposed to during their life cycle.